2021
DOI: 10.1111/twec.13138
|View full text |Cite
|
Sign up to set email alerts
|

The hedge asset for BRICS stock markets: Bitcoin, gold or VIX

Abstract: We compare the weak/strong hedging abilities of three alternative assets, namely bitcoin, gold and US VIX futures, against the downside movements in BRICS stock market indices. Results from the cross-quantilogram approach indicate that bitcoin and gold are weak hedges. Analysis from the recursive sampling shows that each of bitcoin, gold and VIX futures has a time-varying hedging role in some BRICS countries, which has been shaped by the COVID-19 outbreak. Results from the conditional diversification benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 50 publications
6
33
0
Order By: Relevance
“…So in the light of these issues, this study models the reactions of major cryptocurrencies' returns in relation to panic and hysteria incited by This study adds to existing knowledge on three folds. First, it complements findings of recent studies on cryptocurrencies and COVID-19 (Demir et al, 2020;Vidal-Tom as, 2021;Yousaf et al, 2021;Shahzad et al, 2021;Naeem et al, 2021). The focus of recent studies has been directed towards the effect of the prevailing pandemic on stocks (Ozkan, 2021;Curto and Serrasqueiro, 2021;Nguyen et al, 2021;Chen et al, 2021;Mezhgan et al, 2021).…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…So in the light of these issues, this study models the reactions of major cryptocurrencies' returns in relation to panic and hysteria incited by This study adds to existing knowledge on three folds. First, it complements findings of recent studies on cryptocurrencies and COVID-19 (Demir et al, 2020;Vidal-Tom as, 2021;Yousaf et al, 2021;Shahzad et al, 2021;Naeem et al, 2021). The focus of recent studies has been directed towards the effect of the prevailing pandemic on stocks (Ozkan, 2021;Curto and Serrasqueiro, 2021;Nguyen et al, 2021;Chen et al, 2021;Mezhgan et al, 2021).…”
Section: Introductionsupporting
confidence: 57%
“…This has also been supported by Vidal-Tom as (2021) who showed recovery and stability of cryptocurrencies since the first wave of COVID-19 which peaked in March 2020. However, the other groups, including Shahzad et al (2021), Naeem et al (2021), Conlon et al (2020) and Kristoufek (2020), have revealed higher instability and negative returns in cryptocurrencies in comparison to major stock indices such as S&P 500. Majority of these studies have used number of deaths and cases to explain shocks in COVID-19 price volatility though they employed different estimation methods.…”
Section: Research Gapmentioning
confidence: 96%
See 3 more Smart Citations